ANALISIS FAKTOR-FAKTOR PENGEMBANGAN USAHA SIMPAN PINJAM PADA KOPERASI PEGAWAI NEGERIUNIVERSITAS TANJUNGPURA PONTIANAK - Patimah, Patimah; Aminuyati, Aminuyati; Okianna, Okianna (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study aims to determine the factors of developing a savings and loan business at the Civil Servans Cooperative at Tanjungpura University Pontianak. The research method used is descriptive with a form of qualitative research. The subject or informant in this study wasthe management of the Tanjungpura University Civil Servants Cooperative in Pontianak. Data collection tools used in the form of interview guidelines, and documentation. From the results of the study note that from capital, deposits, loans, SHU, the number of members,management, and competitors. But the most influential on the development of savings and loans in the Tanjungpura University Civil Servants Cooperative is capital. Because capital is the main thing for the development of a business entity/cooperative. If the capital is alwaysincreasing, then the loan will automatically run smoothly. Therefore, the size of the capital os very influential for the operation of a savings and loan cooperative.Keywords: Factors for Developing a Savings and Loan Business, Tanjungpura University Civil Service Cooperative